Clinical and Cognitive Functioning Changes After Partial Hospitalization in Patients With Anorexia Nervosa - Tenconi, Elena; Collantoni, Enrico; Meregalli, Valentina; Bonello, Elisa; Zanetti, Tatiana; Veronese, Angela; Meneguzzo, Paolo; Favaro, Angela (Frontiers in Psychiatry, 2021)
Introduction: Anorexia nervosa is usually associated with emotional and cognitive difficulties. Little knowledge is available about the changes in cognitive functioning in patients undergoing treatments. The aim of the present study was to longitudinally assess the impact of partial hospitalization on clini-cal and cognitive functioning in anorexia nervosa. Materials and methods: 56 women with anorexia nervosa according to DSM-5 criteria and 58 healthy women were enrolled in the study. At baseline, all participants underwent clinical, diagnostic and neuropsychological assessment (T0). Patients were also assessed at the end of the treatment pro-gram (T1; n=56). Results: BMI improved significantly throughout treatment. At baseline, patients showed significantly poorer executive abilities and less specific autobiographical memory. After the day-hospital program, decision-making abilities improved significantly. Response to treatment was predicted by BMI at ad-mission and duration of illness, but neuropsychological performance did not contribute to the predic-tion model. Discussion: Cognitive difficulties, mostly regarding executive functions, resulted differently affected by clinical improvement. In particular, while cognitive monitoring and cognitive inhibition appear to be mostly stable trait-like characteristics, decision-making is both more state-dependent and sensitive to clinical status. None of the cognitive variables added information about the response to day hospital treatment; patients with short duration of illness and a rapidly decreasing BMI would benefit more from intensive interventions than less “acute” patients. These observations, if confirmed by future studies, have important clinical implications in order to understand the impact of malnutrition on cognitive functioning and to provide individualized effective treatment for patients with anorexia nervosa.